STUDY OF THE QUALITY OF THE WATER ENVIRONMENT FOR SEAWEED (Eucheuma cottonii) CULTIVATION ON LEMUKUTAN ISLAND, BENGKAYANG REGENCY - Sopia, Viktorina; Munir, Ahmad Mulyadi Sirojul; Hadinata, Fitra Wira (Universitas Mataram, 2025)
Bengkayang Regency is one of the potential areas for the development of seaweed cultivation in the waters of Lumukutan Island, seaweed cultivation cages are spread in the waters of Lemukutan Island located in the West Coast area which is very possible for the development of seaweed cultivation of the Euchema cottonii type. This study aims to determine the quality of the aquatic environment for seaweed cultivation, the suitability of water quality for seaweed cultivation Euchema cottonii on Lemukutan Island, Bengkayang Regency. The method used is a survey method consisting of 3 stations. Sampling with a direct measurement stage in the field, sampling was carried out for 3 months as much as 4 times in a period of 10 days, The results of this study The quality of the aquatic environment for seaweed cultivation that is in accordance with the Quality Standards, namely temperature parameters, depth is only found at station one, current speed, salinity, pH and DO, for the suitability of the quality of the aquatic environment of the cages for seaweed cultivation at stations one, two and three criteria are appropriate.